Juridical Study of Falsification of Power of Sale Deed Made by A Notary Public Official in The Sale and Purchase Without The Consent of The Certificate Owner - Gemilang, Wita Anugrah; Farma Rahayu, Mella Ismelina (Journal of Law, Politic and Humanities, 2024)
Forging a power of attorney deed has serious consequences, including: Legitimate property owners can lose their valuable assets without receiving compensation. It can also cause major financial losses to well-intentioned buyers. A power of attorney deed is a legal document that authorizes someone to sell property on behalf of the legal owner, and is usually made by a notary. Forgery of these documents can occur in various ways, such as forging signatures, using fake identities, collaborating with other parties to manipulate data, or involving corrupt notaries. Forgery of power of attorney deeds has serious impacts, both in the legal and economic realms. In the legal realm, legal owners can lose rights to their property without their knowledge, and the legal process for restoring rights is lengthy and complicated. To prevent forgery of power of attorney deeds to sell, several steps can be taken, including: Notaries must carry out strict verification of the identities and supporting documents of the parties involved in the transaction, including the use of biometric technology and digital verification systems. Increase training and awareness for notaries and their staff regarding document forgery techniques and how to detect them. Development of an integrated information system that allows notaries to check the validity of land certificates and related documents in real-time.